A PLS-SEM Analysis: How Supervisory Problem Affects EFL Undergraduate Thesis Writing Apprehension - Lastika Ary Prihandoko; Joko Nurkamto; Fitria Akhmerti Primasita; Nur Hidayanto Pancoro Setyo Putro; Oikurema Purwati (Universitas Syiah Kuala, 2025)
The supervisory practices, particularly in undergraduate thesis writing, have not received sufficient attention, specifically regarding the impact on EFL students' writing apprehension and the potential gender differences in these dynamics. To fulfil this gap, this study examines the path coefficients among supervisory problem dimensions (research interests, different expectations, limited support, personal relationships, personal conflicts), writing self-efficacy, academic writing competence, toward writing apprehension focusing on the potential gender differences among EFL students. A PLS-SEM analysis was performed on a total of 219 EFL students undertaking their undergraduate thesis writing. The study revealed supervisory problem through mediated variables of academic writing competence and writing self-efficacy influence writing apprehension ( = 0.214 and = 0.509 respectively; p 0.000 for both). Further, the multi-group analysis uncovered notable gender differences. In contrast with male students in which only few paths were statistically significant, all paths were found to be significant for female students. In particular, the path from supervisory problem to academic writing competence had strongest impact on female students, indicating the heightened sensitivity to supervisory problem in relation to the students writing apprehension. These novel findings shed light on the gender differences impact on the academic writing process and that a more pronounced impacts from supervisory problem on their writing apprehension frequently happens to female students. Accordingly, these findings highlight the importance of recognizing and addressing those differences in instructional strategies in order to promote more encouraging and productive learning environment.